Prenatal ultrasound induces apoptotic neurons and Glial Cells (AC) in rabbit fetal brain: a biochemical analysis - Ahmad Zaiki, Farah Wahida; Dom, S. M. (2019)
Ultrasound wave propagates through tissues are absorbed and converted to heat. Findings in numerous studies utilizing the ultrasound exposure have also convinced the existence of ultrasound-induced apoptosis in the exposed cells. Hence, this current study was aimed to detect the apoptotic neurons and glial cells (AC) in the rabbit fetal brain resulting from the prenatal ultrasound exposure. The terminal dUTP nick end-labeling (TUNEL) assay staining by ApopTag® Plus Peroxidase In-Situ Apoptosis Detection Kit (S7101) from Millipore, USA was used. The effects of prenatal ultrasound to neurons and glial cells were analyzed by comparing the AC counts in the rabbit fetal cerebral cross section between the expose and control groups. At least 3 TUNEL stained slides were randomly examined from each subject making a total of N=102 (30 minutes exposure, n= 9; 60 minutes exposure, n= 9; 90 minutes exposure, n= 9; control, n= 7). The temperature increment was measured during the prenatal ultrasound exposure, which the maximum was 1.0, 1.8 and 3.3°C for 30, 60 and 90 minutes of exposure, respectively. Data was analyzed using SPSS version 21.0. The p-values were significant at all stages of gestation with all the p-values were less than 0.001 (p<0.001). The results suggested that there were significant differences in AC counts in all stages of gestation between groups of different exposure duration. The detection of the DNA fragmentation in TUNEL positive cell could serve as an evidence in suggesting the apoptosis was induced by the ultrasound exposure.